Through Animals' Eyes, Again : Stories of Wildlife Rescue - Cuny, Lynn Marie, 1951- (Book collections on Project MUSE., 2006)
Written by the author of "Through Animals' Eyes", this title tells stories that cover the humorous and the tragic, the surprising and the inevitable. It includes stories about the orphaned baby Rhesus monkey who found a new mother in an old monkey rescued from a lab, and the brave red-tailed hawk who was illegally shot, but healed to soar again